Metastatic Crohn's disease despite infliximab therapy - Sara Campos; Inês Coutinho; José Carlos Cardoso; Francisco Portela (Sociedade Brasileira de Dermatologia, 2017)
Abstract Metastatic Crohn's disease is a rare extraintestinal manifestation of Crohn's disease. It is characterized by polymorphic skin lesions formed by non-caseating granulomas located on anatomical sites distant from the gastrointestinal tract. We report a rare case of metastatic Crohn's disease, simultaneously displaying multiple clinically heterogeneous cutaneous lesions, in a patient with previously diagnosed Crohn's disease in remission due to anti-TNF-α use. This case highlights the need for high clinical suspicion and early biopsy in the setting of a patient with Crohn's disease and persistent skin lesions, even under biologic therapy. Furthermore, it reinforces the need of monitoring of the serum level of infliximab, increasing the dose in case it is low or undetectable.